2009
DOI: 10.2139/ssrn.1374288
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Patient Costs Related with Population Morbidity: Can Indirect Costs Affect the Results?

Abstract: A number of health economics works require patient cost estimates as a basic information input.However the accuracy of cost estimates remains in general unspecified. We propose to investigate how the allocation of indirect costs or overheads can affect the estimation of patient costs in order to allow for improvements in the analysis of patient costs estimates. Instead of focusing on the costing method, this paper proposes to highlight changes in variance explained observed when a methodology is chosen. We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…For all the medical procedures (N09, N07D, A48, and N03), the mean of indirect costs calculated by CVU method is in the range between marginal mark‐up and LOS method. Carreras et al () reported that the selection of an overhead allocation methodology does not produce significant distortion of results. Our study did not confirm this finding, indeed, the CVU method is significantly different from LOS method and marginal mark‐up method.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…For all the medical procedures (N09, N07D, A48, and N03), the mean of indirect costs calculated by CVU method is in the range between marginal mark‐up and LOS method. Carreras et al () reported that the selection of an overhead allocation methodology does not produce significant distortion of results. Our study did not confirm this finding, indeed, the CVU method is significantly different from LOS method and marginal mark‐up method.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Step 1: Identify the study question or technologies to be assessed Microcosting studies can be conducted from two main perspectives: healthcare systems (e.g., heart transplant programs) or healthcare facilities (e.g., left ventricular assistance device procedure in hospital settings) [22]. When the first one is used, microcosting supports economic evaluations that guide health policies.…”
Section: Microcosting With the 8-step Tdabc Frameworkmentioning
confidence: 99%
“…Traditional methods usually do not breakdown cost according to the patient's actual utilization [6]. Those methods usually rely on a top-down perspective, which causes a loss of accuracy [22]: for example, the costs of a given department may be divided by the number of beds, including the cost of nursing, and thus it is not possible to explore the level of complexity and resource demanded by individual patients.…”
Section: Healthcare Decision-making Opportunities Using Tdabcmentioning
confidence: 99%
“…La literatura revisada revela que muy pocos trabajos se han referido a establecer los efectos de las metodologías de asignación de CIE en otras variables dependientes, uno de ellos es el de Tan SS, van Ineveld BM, Redekop WK, et al (2009), que se refiere al impacto de cuatro opciones de cálculo de tasas sobre cuatro servicios sanitarios 14 . El segundo trabajo 14 , tuvo como objetivo comparar cuatro opciones de asignación o reparto hacia centros de costos para determinar cuál de ellas permitía una mejor predicción de costos por paciente 15 .…”
unclassified
“…Los estudios publicados muestran un amplio rango de porcentajes de agregación de costos indirectos estructurales a los servicios de salud, que fluctúa entre un mínimo de 10% y un máximo de 44% sobre los costos directos [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
unclassified